2021
DOI: 10.1002/chem.202101520
|View full text |Cite
|
Sign up to set email alerts
|

Driving the Emission Towards Blue by Controlling the HOMO‐LUMO Energy Gap in BF2‐Functionalized 2‐(Imidazo[1,5‐a]pyridin‐3‐yl)phenols

Abstract: Several boron compounds with 2-(imidazo [1,5-a] pyridin-3-yl)phenols, differentiated by the nature of the substituent (R) in the para position of the hydroxy group, have been synthesized and thoroughly characterized both in solution ( 1 H, 13 C, 11 B, 19 F NMR) and in the solid state (X-ray). All derivatives displayed attractive photophysical properties like very high Stokes shift, high fluorescence quantum yields and a good photostability in solution. Time-Dependent Density Functional Theory (TD-DFT) calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Analysis of the lifetime decay curve and determination of absolute quantum yields were done using Fluoracle ® Software package (Version 1.9.1) which runs the FS5 instrument. C1 and C1-BF 2 have been synthesized using an already reported method [41]. All procedures have been done under inert atmosphere following the conventional Schlenk's technique.…”
Section: General Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the lifetime decay curve and determination of absolute quantum yields were done using Fluoracle ® Software package (Version 1.9.1) which runs the FS5 instrument. C1 and C1-BF 2 have been synthesized using an already reported method [41]. All procedures have been done under inert atmosphere following the conventional Schlenk's technique.…”
Section: General Remarksmentioning
confidence: 99%
“…Ligands CX displayed a weak fluorescence and were not thoroughly investigated, while all the boron compounds showed blue fluorescence emission in solution (Figure 2). C1 and C1-BF 2 have been studied previously [41] and are used here as a comparison for the luminescence properties of the novel compounds.…”
Section: Optical Properties In Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transient absorption measurement revealed that the intersystem crossing process from the singlet excited state to triplet excited state causes the low fluorescence quantum yield of 2 . Very recently, S. Brenna and co‐workers reported the substituent effect of phenolic group at 3‐position of 1‐methylimidazo[1,5‐ a ]pyridine‐boron complex [7a] . In this manuscript, we describe the synthesis of blue luminescent boron complexes 3 of 3‐( o ‐hydroxyphenyl)imidazo[1,5‐ a ]pyridine (Figure 1b) and the evaluation of their excited state dynamics to elucidate the effect of phenolic substituent position in boron complex of imidazo[1,5‐ a ]pyridine ligand.…”
Section: Introductionmentioning
confidence: 99%